2023
DOI: 10.1039/d2qi02224a
|View full text |Cite
|
Sign up to set email alerts
|

Using internal strain and mass to modulate Dy⋯Dy coupling and relaxation of magnetization in heterobimetallic metallofullerenes DyM2N@C80and Dy2MN@C80(M = Sc, Y, La, Lu)

Abstract: Endohedral clusters inside metallofullerenes experience considerable inner strain when the size of the hosting cage is comparably small. This strain can be tuned in mixed-metal metallofullerenes by combining metals of...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 122 publications
(190 reference statements)
2
8
1
Order By: Relevance
“…3a and c, Table 1). 79 A similar conclusion was also obtained by Wang et al showing a larger opening of hysteresis in DyY 2 N@C 80 compared to that of DySc 2 N@C 80 . 81…”
Section: Categories Of Emf-smmssupporting
confidence: 79%
See 2 more Smart Citations
“…3a and c, Table 1). 79 A similar conclusion was also obtained by Wang et al showing a larger opening of hysteresis in DyY 2 N@C 80 compared to that of DySc 2 N@C 80 . 81…”
Section: Categories Of Emf-smmssupporting
confidence: 79%
“…3a and c, Table 1). 79 A similar conclusion was also obtained by Wang et al showing a larger opening of hysteresis in DyY 2 N@C 80 compared to that of DySc 2 N@C 80 . 81 In addition to the encapsulated diamagnetic metal that plays an important role in determining the single-ion anisotropy and thus the SMM properties of NCFs, the cage structure Fig.…”
Section: Categories Of Emf-smmssupporting
confidence: 79%
See 1 more Smart Citation
“…Our earlier ab initio studies of LF in conformers of various Dy-SMMs showed that the influence of the lanthanide coordination to the fullerene cage is noticeable but not decisive. 51,119,120 Unexpectedly, the situation found here for NdSc 2 N@C 80 is quite dissimilar. The Δ LF splitting of the 4 I 9/2 multiplet in different conformers varies from 690 to 1018 cm −1 , and even larger relative variation is found for Δ 1,2 , which spans from 80 to 470 cm −1 (Fig.…”
Section: Synthesis and Molecular Structurecontrasting
confidence: 65%
“…In contrast, the ab initio description of the isostructural DySc 2 N@C 80 is entirely consistent with expectations for a strongly axial ligand eld. 45,120 The ground state KD1 has 99.7% weight of the j±15/2i state and g x,y is less than 10 −4 , while g z = 19.84 (versus 20.00 expected for the pure m J = ±15/2 state). 120 The next three KDs of DySc 2 N@C 80 also have high contribution of one of the j±m J i states (>80%), and the principal z axes of their pseudospin g-tensors are nearly collinear.…”
Section: Photoluminescence and Ligand-eld Splittingmentioning
confidence: 97%